'Naloxone works': The politics of knowledge in 'evidence-based' drug policy. (May 2017) - Lancaster, Kari; Treloar, Carla; Ritter, Alison
For over 20 years, drug policy experts have been calling for the wider availability of naloxone, to enable lay overdose witnesses to respond to opioid overdose events. However, the 'evidence base' for peer-administered naloxone has become a key point of contention. This contention opens up critical questions about how knowledge ('evidence') is constituted and validated in drug policy processes, which voices may be heard, and how knowledge producers secure privileged positions of influence. Taking the debate surrounding peer-administered naloxone as a case study, and drawing on qualitative interviews with individuals (n = 19) involved in the development of naloxone policy in Australia, we examine how particular kinds of knowledge are rendered 'useful' in drug policy debates. Applying Bacchi's poststructuralist approach to policy analysis, we argue that taken-for-granted 'truths' implicit within evidence-based policy discourse privilege particular kinds of 'objective' and 'rational' knowledge and, in so doing, legitimate the voices of researchers and clinicians to the exclusion of others. What appears to be a simple requirement for methodological rigour in the evidence-based policy paradigm actually rests on deeper assumptions which place limits around not only what can be said (in terms of what kind of knowledge is relevant for policy debate) but also who may legitimately speak. However, the accounts offered by participants reveal the ways in which a larger number of ways of knowing are already co-habiting within drug policy. Despite these opportunities for re-problematisation and resistance, the continued mobilisation of 'evidence-based' discourse obscures these contesting positions and continues to privilege particular speakers.